1 and 5 Day Differential INSAR Under Crossing Orbits with TerraSAR-X - Wollstadt, Steffen; Lopez-Dekker, Paco; Prats-Iraola, Pau; De Zan, Francesco; Busche, Thomas; Krieger, Gerhard (2012 IEEE International Geoscience and Remote Sensing Symposium, 2012)
This paper presents investigations on a one year time series of crossing orbit differential interferometry SAR acquisitions with a 1-, 5- and 6-days temporal baseline. The conditions for crossing orbit interferometry are briefly discussed as the requirement of a common ground spectrum has to be satisfied. The uniquely short revisit times give the opportunity to perform interferometry on a glacier area, i.e. the Ronne ice-shelf, in X-band. The coherence results over one year as well as surface velocity measurements are shown and discussed.